Investigating the effects of dollarization on economic growth in Zimbabwe (1990-2015) - Nemaramba, Nhongerai (Research of GSB, 2019)
This research presents a comprehensive analysis of Zimbabwe’s adoption of a basket of foreign currencies as legal tender and the resultant economic effects of this move. Upon adoption in 2009, Zimbabweans were optimistic about the future as they thought the multicurrency regime would bring a more stable economy. Eight years down the line, it is prudent to evaluate whether this optimism was justified in terms of the effect of the policy on the Zimbabwean economy. An econometric model was applied in this study to investigate how dollarization and the other macroeconomic factors impacted on economic growth. The findings of the study show that most macroeconomic indicators improved as a result of dollarization. The average economic growth rate, as measured by growth in gross domestic product, was -5.22 per cent for the period before dollarization (1990 to 2008) and 14.83 per cent for the dollarized period (2009 to 2015). The difference in average growth rate is 20.05 per cent and is statistically significant at 1 per cent. This implies that the average economic growth rate improved by 20.05 per cent after the economy was dollarized. The average GDP per capita improved during dollarization by $278.78 and this difference is statistically significant at the 1 per cent level. Foreign direct investment inflows per capita improved from the pre-dollarization average of $5.40 to an average of $20.89 during the dollarized period, with this difference statistically significant at the 1 per cent level. Inflation declined substantially from over 230 million per cent to an average of less than 1 per cent during the dollarized period. However, despite a significant improvement in some macroeconomic variables, Zimbabwe’s debt increased during dollarization. The results from the regression model of economic growth on its determinants further show that dollarization improved economic growth. In the absence of a dummy variable for dollarization, economic growth is influenced by population (statistically significant at 10 per cent), literacy (statistically significant at 5 per cent) and inflation (statistically significant at 1 per cent). However, with a dollarization dummy, growth becomes a function of inflation (statistically significant at 1 per cent) and dollarization (statistically significant at 10 per cent). The findings generally indicate that dollarization has improved economic growth. They point to the policy implication that a control of inflation to reasonable levels is crucial for economic growth. The policy implications for such findings are discussed in the study